Effectiveness of the Internal Control System Against Fraud Tendencies Meta-Analysis Study - Faisol, Faisol; Haryadi, Bambang; Musyarofah, Siti; Iswahyudi, Anggi Pradhita (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
The aim of this research is to evaluate the impact of internal control on fraud tendencies. This research uses a meta-analysis approach by reviewing comparable previous studies. This study invloves 20 previous studies published from 2017 to 2021 with themes related to the effect of internal control systems on fraud tendencies as the research sample. The aim of using the most recently published research is to maximize the effectiveness of this research. The JASP (Jaffreys Amazing Statistical Application) and Microsoft Excel programs are used to process the data in the meta-analysis. The outcome show that internal control system has a negative and significant effect on fraud tendencies. This is consistent with the theory and results of previous studies which show that the more effective the internal control system is implemented, the less likely fraud to occur in organizations. Therefore, based on the findings of this study, businesses and governmental organizations must have internal control systems in place to lessen the likelihood of fraud